Perbandingan Kualitas Layanan Karyawan Salon Lulusan SMK Kecantikan dan Non-Kecantikan di Bukittinggi - Hanafi, Luthfia Azhmi; Saputra, Indra; Rahmiati, Rahmiati; Yanita, Merita (Lembaga Yasin AlSys, 2025)
Differences in employees' educational backgrounds are presumed to influence the quality of salon services received by customers, particularly in terms of professionalism and technical competence. This study aims to compare the service quality between salon employees who are graduates of vocational high schools in beauty (SMK Tata Kecantikan) and those from general or non-beauty vocational high schools (SMA/SMK non-kecantikan). Using a quantitative comparative approach, the research involved customer participants from two salons in Bukittinggi City. Data were collected through a closed-ended questionnaire using a 4-point Likert scale and analyzed using the Independent Sample t-Test with SPSS version 0.25. Prior to hypothesis testing, normality (Shapiro-Wilk) and homogeneity (Levene’s Test) checks were conducted. Descriptive analysis showed that beauty school graduates outperformed in the aspects of tangibles, reliability, and empathy but scored lower in assurance. Conversely, non-beauty graduates excelled in reliability, responsiveness, assurance, and empathy, but were weaker in tangibles. However, the t-test results indicated no significant difference in overall service quality between the two groups (p = 0.894 > 0.05). The study concludes that formal educational background does not significantly affect customer perceptions of salon service quality. These findings offer practical implications for salon managers to prioritize training and work experience over educational background in employee recruitment.